2023
DOI: 10.1302/0301-620x.105b2.bjj-2022-0685.r1
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre comparative analysis of fixation versus revision surgery for periprosthetic femoral fractures following total hip arthroplasty with a cemented polished taper-slip femoral component

Abstract: Aims The aim of this study was to compare open reduction and internal fixation (ORIF) with revision surgery for the surgical management of Unified Classification System (UCS) type B periprosthetic femoral fractures around cemented polished taper-slip femoral components following primary total hip arthroplasty (THA). Methods Data were collected for patients admitted to five UK centres. The primary outcome measure was the two-year reoperation rate. Secondary outcomes were time to surgery, transfusion requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…We were delighted to see this large multicentre study from Leeds (UK) that aimed to compare, in large numbers, the treatment options of open reduction and internal fixation (ORIF) with revision surgery (of all types) for patients presenting with Unified Classification System (UCS) type B periprosthetic femoral fractures around cemented polished taper-slip stem. 3 The study was conducted at five large UK centres retrospectively, and included follow-up to two years for reoperation, surgical outcomes (including wait for surgery, blood loss, length of stay, and complications), and mortality rates. The study cohort consisted of 317 periprosthetic fractures (in 317 patients) with a median follow-up of 3.6 years.…”
Section: Fixation Better Than Revision In Type B Periprosthetic Fract...mentioning
confidence: 99%
“…We were delighted to see this large multicentre study from Leeds (UK) that aimed to compare, in large numbers, the treatment options of open reduction and internal fixation (ORIF) with revision surgery (of all types) for patients presenting with Unified Classification System (UCS) type B periprosthetic femoral fractures around cemented polished taper-slip stem. 3 The study was conducted at five large UK centres retrospectively, and included follow-up to two years for reoperation, surgical outcomes (including wait for surgery, blood loss, length of stay, and complications), and mortality rates. The study cohort consisted of 317 periprosthetic fractures (in 317 patients) with a median follow-up of 3.6 years.…”
Section: Fixation Better Than Revision In Type B Periprosthetic Fract...mentioning
confidence: 99%
“…In another single-centre study, Slullitel et al 16 also found that selected B2 fractures around PTS stems can be safely treated with fixation. Most recently, Jain et al 17 reported the results of a large multicentre study on 317 periprosthetic fractures around PTS stems managed across five UK centres and found that fixation surgery (n = 167) was associated with lower reoperation rates, lower local complication rates, a shorter time to surgery, and lower critical care requirements than revision arthroplasty (n = 150). Specifically, for type B2 and B3 fractures there was no difference in reoperation rate at two years between fixation and revision arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Our clinical outcomes have been published previously. 15,17,[19][20][21][22][23] This paper details our experience of which UCS type B fractures around cemented PTS stems cannot, or should not, be treated with fixation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations